The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7554/elife.54795
|View full text |Cite
|
Sign up to set email alerts
|

Metapopulation ecology links antibiotic resistance, consumption, and patient transfers in a network of hospital wards

Abstract: Antimicrobial resistance (AMR) is a global threat. A better understanding of how antibiotic use and between-ward patient transfers (or connectivity) impact population-level AMR in hospital networks can help optimize antibiotic stewardship and infection control strategies. Here, we used a metapopulation framework to explain variations in the incidence of infections caused by 7 major bacterial species and their drug-resistant variants in a network of 357 hospital wards. We found that ward-level antibiotic consum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
(81 reference statements)
0
9
1
1
Order By: Relevance
“…While we were able to identify factors that associate with elevated or reduced levels of resistance at such large scales, we note that over shorter timescales and more localized spatial scales key factors may differ. For example, we did not find an effect of total drug use on resistance, but drug use is known to drive resistance increases at finer scales such as within individual hospitals or countries 30,52,53 . We also note that being an observational study, the associations identified here are not necessarily causative.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…While we were able to identify factors that associate with elevated or reduced levels of resistance at such large scales, we note that over shorter timescales and more localized spatial scales key factors may differ. For example, we did not find an effect of total drug use on resistance, but drug use is known to drive resistance increases at finer scales such as within individual hospitals or countries 30,52,53 . We also note that being an observational study, the associations identified here are not necessarily causative.…”
Section: Discussioncontrasting
confidence: 59%
“…In fact, our results demonstrate that among the various factors implicated in resistance evolution, being nosocomial is one of the most statistically robust predictors (Table 2). The high prevalence of antibiotic resistance among nosocomial pathogens is largely attributed to the interplay of high antibiotic usage, which may impose selection for resistance, and imperfect infection control practices, which may promote transmission of resistant pathogens in hospitals [29][30][31] . These results highlight the importance of developing protocols to further minimize pathogen transmission within hospitals, for example, by improving sterilization and hygiene practices.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our goal was to study how ecological mechanisms impact average epidemiological outcomes in the context of different model assumptions and parameter uncertainty, and in this context, ODE modeling was the more appropriate tool, particularly for widely endemic ARB like C. difficile , MRSA and ESBL-EC. Still, further insights could certainly be gained by accounting for additional complexity and stochastic heterogeneity in future work, from within-host spatial organization ( Estrela et al, 2015 ), to patient and staff contact behavior ( Duval et al, 2019 ), to inter-institutional or inter-ward meta-population dynamics ( Shapiro et al, 2020 ). These distinctions may be particularly important for rare or non-endemic ARB (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…(Niewiadomska et al, 2019) Here, microbiome competition was found to have a large impact on incidence but comparatively little impact on resistance ratesboth for the theoretical pathogen evaluated in Part 1 (Figures 3, 4) and for the four ARB (Estrela et al, 2015) to patient and staff contact behaviour, (Duval et al, 2019) to inter-institutional or inter-ward meta-population dynamics. (Shapiro et al, 2020) These distinctions may be particularly important for rare or nonendemic ARB (e.g. CP-KP in some regions).…”
Section: Microbiome Ecology Underlies Epidemiological Responses To Public Health Interventionsmentioning
confidence: 99%
“…Now, in eLife, Jean-Philippe Rasigade and co-workers from Université de Lyon and the Hospices Civils de Lyon – including Julie Teresa Shapiro as first author – report how seven species of bacteria, and their resistant strains, spread across 357 wards of a major hospital organisation in Lyon ( Shapiro et al, 2020 ). To do this, the team adapted a model that is often used in ecology to study populations of animal species that live in, and migrate between, different locations.…”
mentioning
confidence: 99%